2011
DOI: 10.1038/leu.2011.265
|View full text |Cite
|
Sign up to set email alerts
|

Notch is an essential upstream regulator of NF-κB and is relevant for survival of Hodgkin and Reed–Sternberg cells

Abstract: A major pathogenetic mechanism in classical Hodgkin lymphoma (cHL) is constitutive activation of canonical nuclear factor-jB (NF-jB) p50/p65 signaling, controlling lymphoma cell proliferation and survival. Recently, we demonstrated that aberrant Notch1 activity is a negative regulator of the B cell program in B cell-derived Hodgkin and Reed-Sternberg (HRS) cells. Despite abundant evidence for a complex contextdependent cross talk between Notch and NF-jB signaling in hematopoietic cells, it is unknown whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 34 publications
3
56
0
Order By: Relevance
“…The role of alternative NF-kB activation pathway in cancer cells remained unclear. Several reports showed that Notch1 regulated the expression of p52 and RelB (35,36). Because, as far as we know, it is the first report to show the interaction of Notch1 and RelB, these findings may be a novel mechanism for regulation of the alternative NF-kB activation pathway by Notch1.…”
Section: Discussionmentioning
confidence: 87%
“…The role of alternative NF-kB activation pathway in cancer cells remained unclear. Several reports showed that Notch1 regulated the expression of p52 and RelB (35,36). Because, as far as we know, it is the first report to show the interaction of Notch1 and RelB, these findings may be a novel mechanism for regulation of the alternative NF-kB activation pathway by Notch1.…”
Section: Discussionmentioning
confidence: 87%
“…Notch dimerization leads to strong proliferation and apoptosis resistance [48]. Recently, Notch signaling was also showed to be an upstream regulator of NF-kB [49], providing a cross-link between these two pathways.…”
Section: Dysregulated Signaling Pathwaysmentioning
confidence: 99%
“…HCMV infection downregulates Notch1, NICD1, and Jag1 proteins. HCMV is known to manipulate NF-B and epithelial growth factor receptor (EGFR) signaling pathways for efficient entry and replication (37,38), and both pathways have cross talk with the Notch signaling pathway (39,40). To determine whether HCMV infection alters Notch pathway protein levels, NPCs were mock or virus infected at an MOI of 3 and Notch1, NICD1, and Jag1 were detected by Western blotting.…”
Section: Hcmv Infection Inhibits Transcription Of Notch1 and Jag1mentioning
confidence: 99%